Effect of differential oral dose administration of aqueous leaf extract of Senna occidentalis, Annona muricata and Aju Mbaise on serum electrolyte levels in Albino rats - Etu, Esther Ifeyinwa; Umeano, Chiagozie Chinyere; Wike, Nyejirime Young; Chibueze, O. Odeh; Richards, Ndubuisi Nonso; Etu, Kenneth Eze; Mmesomachi, Uche Bethel; Maduka, Chinedu Pascal; Jennifer, Ekoh Adaorah; David, Chukwu Chigozie; Chinedu, Gabriel Silas; Esochaghi, Chiamaka; et al. (Journal of Medicinal Herbs and Ethnomedicine, 2024)
Electrolyte imbalances are frequent in medical practice, mostly seen in hospital populations, affecting a wide range of patients and linked to higher rates of morbidity and death. Herbal medicine has been the most accessible and economical form of treatment and it has demonstrated significant promise for the management of a variety of health issues. This study evaluated the effect of differential oral dose administration of aqueous leaf extract of Senna occidentalis, Annona muricata and Aju Mbaise on serum electrolyte levels in albino rats. Twenty Albino rats were used for this study. The rats were grouped into four with 4 rats each. Oral administration of S. occidentalis, A. muricata and Aju Mbaise were carried out at different doses (200, 400 and 500 mg kg-1 respectively) for 4 weeks. The rats were sacrificed by jugular decapitation 24 hours after the last administration of the extract and blood samples were collected for serum electrolyte analysis. The result revealed a significant increase p<0.05 for chloride, bicarbonate, sodium and potassium ions for the leaf extracts of S. occidentalis, A. muricata and Aju Mbaise. This implies that the leaves of these plants can be toxic and it is therefore advised that consumption of these leaves should be at therapeutic doses since it is associated with an increase in electrolyte levels.